DNA sequences responsible for tissue-specific expression of a chicken alpha-crystallin gene in mouse lens cells. - Okazaki, K (1985)
We have studied the DNA sequences required for high-level expression of a cloned chicken alpha-crystallin gene by introducing a hybrid alpha/delta-crystallin gene into nuclei of mouse lens epithelial cells in primary culture. The level of transient expression of the hybrid gene consisting of the 5' upstream promoter region of the alpha-crystallin gene fused to the structural portion of the delta-crystallin gene was determined by Western blot analysis using anti-delta-crystallin serum. The hybrid gene appears to be expressed in a tissue-specific manner, since it is active in mouse lens cells but not in fibroblasts or in L cells. The DNA sequences located 242-189 bp upstream from the transcription initiation site are required for high-level expression in lens cells. They are active when their orientation is reversed at the original site or when placed approximately 1.7 kbp downstream from the cap site in the second intron of the hybrid gene in either orientation. When these DNA sequences were replaced by the enhancer sequences of Moloney murine leukemia virus, the hybrid gene was expressed in both lens cells and fibroblasts.